Does Idiosyncratic Risk Matter? Evidence from the Philippine Stock Market - V. Nartea, Gilbert; D. Ward, Bert (Asian Journal of Business and Accounting, 2017)
This research examines if the three main empirical findings on idiosyncratic volatility (IV) in the US market also apply to small but open emerging markets such as the Philippines. Our results indicate that we cannot generalise the US findings for the Philippine stock market. First, contrary to the US findings of Campbell, Lettau, Malkiel and Xu (2001), we do not find a trend in idiosyncratic volatility over our study period. Second, we find that average equal-weighted idiosyncratic volatility is negatively related to market returns, which is opposite to the findings of Goyal and Santa-Clara (2003) for the US market. Third, we find no relation between IV and abnormal returns, contrary to the findings of Ang, Hodrick, Xing and Zhang (2006), and Brockman and Yan (2006) for the US market.